DETEKSI DAN PEREKRUTAN KASUS KELAINAN BAWAAN SISTEM SARAF PUSAT DI PUSKESMAS WILAYAH KOTA JAYAPURA - Hendrikus Masang Ban Bolly (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2022)
AbstractCongenital central nervous system abnormalities occur in the fruit of pregnancy and are recognized when the newborn is born birth or detected on ultrasound examination when the baby is still in the womb. Master key The management of infants/children with congenital abnormalities of the central nervous system is detection and correction feature maybe. Public outreach activities and training of health workers This puskesmas aims to introduce, help detect and refer to neurosurgeons for necessary medical intervention. Methods of implementing activities include counseling the general public and health workers are carried out through bold Zoom Meeting media; power training special health services are carried out directly at the Puskesmas using the booklet “The Difference Behind Sheets Congenital Brain and Spine”. The training with this theme is the first time it has been conducted in Jayapura, even in Papua. The results that have been achieved from this series of community service programs are: educating the general public and health workers in a courageous manner, special training for health workers Puskesmas and obtained a copyright registration letter from the Ministry of Law and Human Rights of the Republic of Indonesia for the Booklet product Flipchart of Inherited Differences in the Central Nervous System. Abstrak Kelainan bawaan system saraf pusat terjadi sejak dalam buah kehamilan dan diketahui saat bayi baru lahir maupun terdeteksi pada pemeriksaan ultrasonografi saat bayi masih dalam kandungan. Kunci utama penatalaksanaan bayi/anak dengan kelainan bawaan system saraf pusat adalah deteksi dan koreksi kelainan sedini mungkin. Kegiatan penyuluhan masyarakat awam dan pelatihan tenaga kesehatan puskesmas ini bertujuan untuk mengenalkan, membantu mendeteksi dan merujuk ke tenaga ahli bedah saraf untuk dilakukan intervensi medis yang diperlukan. Metode pelaksanaan kegiatan meliputi penyuluhan masyarakat awam dan tenaga kesehatan dilakukan melalui media daring Zoom Meeting; pelatihan tenaga kesehatan khusus dilakukan langsung di Puskesmas menggunakan booklet “Lembar Balik Kelainan Bawaan Otak dan Tulang Belakang”. Pelatihan dengan tema ini merupakan yang pertama kali dilakukan di Jayapura, bahkan di Papua. Hasil yang telah dicapai dari rangkaian program pengabdian ini adalah penyuluhan masyarakat awam dan tenaga kesehatan secara daring, pelatihan khusus tenaga kesehatan Puskesmas serta diperolehnya surat pencatatan hak cipta dari Kemkumham RI untuk produk Booklet Lembar Balik Kelainan Bawaan Sistem Saraf Pusat.